Obesity and fracture healing - M.S. Patil; Hashmi Baseer (Al Ameen Medical College, 2017)
Background: Obesity is an independent risk factor in trauma related morbidity. This study described the prevalence of obesity/overweight in children and adolescents reporting a recent fracture in relation to fracture healing and associated complications. Methods: In this prospective randomized controlled study. 52 cases were enrolled with various fractures, who underwent definitive treatment either conservative / operative. All patients were classified in various categories depending upon their BMI, after calculating their height and weight according to WHO standards. All patients were followed up for at least 4 months with monitoring clinically and radiologically at 6th, 12th weeks and there after once a month for evaluation of status of bone healing and complications. Results: Average healing time was 8.4 weeks. In case of pre obese it was 7.07 weeks with P < 0.09. In class I Obese, it was 8.8 weeks with P <0.001. In class II Obese, it was 7.6 weeks with P <0.005 and in class III, it was 9.5 weeks with P<0.005. After applying t value and P value we found that there is significant delay in healing time, in patients belonging to higher obese class accompanied by complications. Conclusion: We found significant increase in fracture healing time with higher BMI and also associated complications.